A Gorgon's mask : the mother in Thomas Mann's fiction - Lawson, Lewis A. (Psychoanalyse en cultuur, 2005)
The thesis of A Gorgon's mask: The Mother in Thomas Mann's Fiction depends upon three psychoanalytic concepts: Freud's early work on the relationship between the infant and its mother and on the psychology of artistic creation, Annie Reich's analysis of the grotesque-comic sublimation, and Edmund Bergler's analysis of writer's block. Mann's crisis of sexual anxiety in late adolescence is presented as the defining moment for his entire artistic life. In the throes of that crisis he included a sketch of a female as Gorgon in a book that would not escape his mother's notice. But to defend himself.